AGRONOMIC BIOFORTIFICATIONS OF TEFF (ERAGROSTIS TEF): FROM SOIL PROPERTIES TO ZINC FERTILIZERS APPLICATION STRATEGIES IN ETHIOPIA - Desta, Mesfin (2025)
Most Ethiopian soils are low in plant available zinc (Zn), and this varies with the landscape position and soil type. This affects grain Zn loadings and subsequently human health when diets are primarily based on cereals grown on these soils. The link from soil – plant - human is strong and unlocking Zn availability in the soil helps efforts for improved nutrition and health in Ethiopia. Therefore, a better understanding of soil properties (Chapter 3 and 4) and devising best fit fertilizer application strategies (Chapter 5 and 6) are important for increasing grain Zn loading by crops, biofortifying crops with Zn.